Evaluation of frontlimb flexor tendinitis in horses by ultrasonographic examination - Mustafa Arıcan; Kerim Nida Çalım; Ayşe Kocabıyık; Ünal Yavuz (Eurasian Journal of Veterinary Sciences)
In this study, the normal and abnormal proportions of the flexor tendons of forelimbs of healty and tendinitis throughbred horses were measured ultrasonographically. Dimensions, circumferences and cross-sectional areas of the superficial digital flexor tendon (SDFT), deep digital flexor tendon (DDFT), check ligament (CL) and suspensory ligament (SL) were measured. The determination of the physiological boundaries of those tendons were aimed. The horse which are used in the study are 2-4 years old, in healty 19 and 6 horses with tendinitis throughbreds these measurements were applicated. Throughbred english horse area 2 for circumferences values of the MFDS were 0.869 + 0.453 cm2, MFDD values were 1,062 + 0.510 cm2, IC values were 1,324 + 0.647 cm2 and the horses with tendinitis values of the MFDS (0.625 + 0.181), MFDD (0.830 + 0.285) and LA (0.687 + 0.220) cm2 were estimated. There are no differences between two groups by statistically. Area 2 for lenght values of the MFDS were 1.615 + 0.649 cm, MFDD values were 1.698 + 0.600 cm, IC values were 2.078 + 0.665 cm, the horses with tendinitis values of the MFDS (1.213 + 0.335) cm, MFDD (1.303 + 0.160), ve LA (1.413 + 0.349) cm were evaluated. Especially, MFDD tendon and LA tendon show statistically differences between compared to normal one concern about lenght of tendon. As a conclusion, healty thoroughbred English horses and horses with tendinitis of flexor tendons of forelimbs were determined of morphometric measurements by ultrasonographically. The standard measurements were compared to tendinitis group and other breeds.